2017
DOI: 10.3389/fphar.2017.00137
|View full text |Cite
|
Sign up to set email alerts
|

BGP-15 Protects against Oxaliplatin-Induced Skeletal Myopathy and Mitochondrial Reactive Oxygen Species Production in Mice

Abstract: Chemotherapy is a leading intervention against cancer. Albeit highly effective, chemotherapy has a multitude of deleterious side-effects including skeletal muscle wasting and fatigue, which considerably reduces patient quality of life and survivability. As such, a defense against chemotherapy-induced skeletal muscle dysfunction is required. Here we investigate the effects of oxaliplatin (OXA) treatment in mice on the skeletal muscle and mitochondria, and the capacity for the Poly ADP-ribose polymerase (PARP) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 93 publications
(136 reference statements)
0
50
1
1
Order By: Relevance
“…Given that mice 8 weeks of age are still growing, reduced weight gain in this population may persist in older mice, and we have observed that body weight gain remains significantly reduced for >60 days in mice treated with the extended regimen (30‐mg/kg oxaliplatin cumulative dose). Although food intake was not measured in this model, a recent publication found that oxaliplatin treatment caused weight loss without a significant reduction in food or water intake in mice, suggesting that muscle loss was independent of chemotherapy‐associated anorexia . Interestingly, Barreto et al .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Given that mice 8 weeks of age are still growing, reduced weight gain in this population may persist in older mice, and we have observed that body weight gain remains significantly reduced for >60 days in mice treated with the extended regimen (30‐mg/kg oxaliplatin cumulative dose). Although food intake was not measured in this model, a recent publication found that oxaliplatin treatment caused weight loss without a significant reduction in food or water intake in mice, suggesting that muscle loss was independent of chemotherapy‐associated anorexia . Interestingly, Barreto et al .…”
Section: Discussionmentioning
confidence: 95%
“…One study, using a similar apparatus, showed that oxaliplatin reduces the total distance traveled in mice (representing locomotive behavior) . Other studies suggested that nosepoke (exploratory/escape behavior) was non‐significantly reduced in oxaliplatin‐treated rats and voluntary exploratory behavior in oxaliplatin‐treated mice was unaltered when measured over a 24‐hour period . The voluntary exploratory behavior included interaction with food and water, which was independently significantly increased in oxaliplatin‐treated mice, and this may have confounded aspects of these results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations